Developing real life experience through teaching culture in the EFL class: fostering the learning trough intercultural awareness (2013)
In order to know how university can give learners useful tools to develop the communicative competence into the English class, it is necessary to implement different kind of activities that involve the students in a curriculum of meaningful content. One of the aspects to take into account is the inclusion of Culture in the learning process in English classes. One of the key components in language is Culture. Culture, however, varies from one country to another and from one community to another within that country. Due to the diversity of cultures, it is important for teachers to know the culture that is going to be taught in the language-learning classroom. The problem state by the author is that culture is not part of the curriculum in many universities due to the fact that teachers leave behind the role of culture in the EFL because teachers are not culturally aware, the extra time devoted to activities and the limited span of time to complete the syllabi in a semester. Moreover, the author argues that universities neglect to teach culture due to students’ negative attitude towards the target culture.